Adverse maternal and neonatal outcomes in adolescent pregnancy - Kawakita, Tetsuya (J Pediatr Adolesc Gynecol, 2015)
STUDY OBJECTIVE: To investigate the outcomes of adolescent pregnancy. DESIGN: Retrospective cohort study from the Consortium on Safe Labor between 2002 and 2008. SETTING: 12 clinical centers with 19 hospitals in the United States. PARTICIPANTS: 43,537 nulliparous women <25 years, including 1,189 younger adolescents (age ≤15.9), 14,703 older adolescents (age 16–19.9)], and 27,645 young adults (age 20–24.9). INTERVENTIONS: aOR with 95%CI were calculated, controlling for maternal characteristics and pregnancy complications (young adults as a reference group). MAIN OUTCOME MEASURE: Maternal, neonatal outcomes, cesarean indications, and length of labor. RESULTS: Younger adolescents had increased risk of maternal anemia (aOR=1.25; 95%CI=1.07–1.45), preterm delivery <37 weeks of gestation (aOR=1.36; 95%CI=1.14–1.62), postpartum hemorrhage (aOR=1.46; 95%CI=1.10–1.95), preeclampsia/HELLP syndrome (aOR=1.44; 95%CI= 1.17–1.77) but had decreased risk of cesarean delivery (aOR=0.49; 95%CI= 0.42–0.59), chorioamnionitis (aOR=0.63; 95%CI=0.47–0.84), and neonatal intensive care unit (NICU) admission (aOR=0.80; 95%CI=0.65–0.98). Older adolescents had increased risk of maternal anemia (aOR=1.15; 95%CI= 1.09–1.22), preterm delivery at <37 weeks of gestation (aOR=1.16; 95%CI=1.08–1.25), and blood transfusion (aOR=1.21; 95%CI=1.02–1.43), but had decreased risk of cesarean delivery (aOR=0.75; 95%CI= 0.71–0.79), chorioamnionitis (aOR=0.83; 95%CI=0.75–0.91), major perineal laceration (aOR=0.82; 95%CI= 0.71–0.95), and NICU admission (aOR=0.89; 95%CI=0.83–0.96). Older adolescents were less likely to have cesarean for failure to progress or cephalopelvic disproportion (aOR=0.89; 95%CI 0.81–0.98). For adolescents who entered spontaneous labor, second stage of labor was shorter (P<.01). CONCLUSION: Adolescents were less likely to have cesarean delivery. Failure to progress or cephalopelvic disproportion were decreased in older adolescents. Adolescents who entered spontaneous labor had shorter second stage of labor.